Traditional Chinese medicine physicians’ insights into inter-professional tensions between traditional Chinese medicine and biomedicine: a critical perspective - Chang, Leanne; Lim, Jing Ci Jill (Taylor & Francis, 2017)
In Singapore, the institutional preference for biomedicine and the cultural importance of traditional Chinese medicine (TCM) have created tensions between the two medical systems and erected barriers to a more collaborative healthcare system. This study foregrounds TCM physicians’ voice to reveal ideological struggles and power imbalances that underlie the inter-professional tensions and accompanying marginalization of TCM. Through in-depth interviews with 22 TCM physicians in Singapore, this study reveals the incongruences in ideological underpinnings between biomedicine and TCM, reflected in their different worldviews and epistemological approaches to knowledge formation and evaluation. Power differentials between the two medical systems are manifest in TCM physicians’ inferior position in relation to their biomedical peers, the patients’ internalization of biomedical standards to question the TCM profession and their own interest in seeking TCM treatments, and the state’s limited support for TCM research, subsidies, and service provision in hospital settings. The results suggest that more open dialogue about the dichotomous framings of biomedicine and TCM is key to disrupting the mutual reinforcement of ideology and power, as well as to creating increased mutual understanding between the two medical systems.